Immediate psychological impact of dental students on COVID-19 epidemic in India - A cross sectional study - Saravanan Kandasamy; Reena Rachel John; Arunkumar Jayaraman; Suresh Chinnakutti; Manoj Chandrasekar; D Y Mallikarjunan (Wolters Kluwer Medknow Publications, 2021)
Introduction: The 2019 coronavirus disease (COVID-19) epidemic is a global health threat and is by far the largest outbreak of atypical pneumonia since after SARS over the past few decades. Within weeks of the initial outbreak the total number of cases and deaths exceeded those of SARS. Such mass Casualties often trigger waves of heightened fear and anxiety in many population. Aim: To assess the psychological impact and mental health status among the dental students studying in the Vinayaka Mission's Sankarachariyar Dental College, Salem, India. Materials and Method: A total of 21 psychological state questionnaires along with demographic aspects were distributed to 460 under graduate dental students from Vinayaka Mission's Sankarachariyar Dental College, Salem, Tamilnadu. The Psychological state was assessed using the Depression, Anxiety and Stress Scale (DASS). Results: 404 questionnaires were taken for our study as they responded all questions. The results were calculated based on the responses obtained year wise, gender, Place of residence, Living with family, Steady family income and Acquaintance affected with covid and compared among the three psychological assessments Depression, Anxiety and stress. The results of the study were done using SPSS (V21.0IBM, Chicago) Software. Conclusion: We attempted to correlate the socio demographic datas with psychological status of the dental students' in our university using the DAS scale. This study focused on the need for treating the psychological impact of the society at this outbreak as the mental health is the most important to deal with.